The association between caries related treatment needs and socio-demographic variables among young Israeli adults: a record based cross sectional study - Levy, Dan Henry (Isr J Health Policy Res, 2018)
BACKGROUD: The need for dental treatments, especially those related to dental caries, may be associated with and influenced by a wide range of demographic variables. The aim of this study was to describe caries related treatment needs among young Israeli adults and the association with several socio-demographic factors, including socio-economic cluster (SEC), intellectual capabilities, ethnicity and other variables. METHODS: Data were collected from dental records of army recruits between 2012 and 2013. We cross-examined data regarding dental treatment needs with socio-demographic variables: age, gender, SEC, intellectual capability score (ICS), birth place of participant and parents, education and immigration. RESULTS: Data received regarding 13,398 combat recruits during their first four months of military training. Most subjects were males (92.4%), with a mean age of 18.9 years. 10.8% were immigrants, with 12.2 years living in Israel before their recruitment. Only 17.7% had no dental treatment needs. Mean number of teeth needing treatment was: for restorations 1.96 ± 2.59, for root canal therapies 0.07 ± 0.44 and for extractions 0.05 ± 0.28. Low ICS scores and low SEC group were significantly associated with higher treatment needs (P < 0.001). Statistically significant higher treatment needs were observed among participants who originated from immigrant families. In a multivariate analysis (Generalized Linear Model), gender, age, ICS score, SEC group and country of birth were found as independent predictors for number of restorations needed. CONCLUSION: Socio-demographic variables significantly influence dental treatment needs and should be taken into account when preparing intervention programs in this population.